Have Capital Market Anomalies Attenuated in the Recent Era of High Liquidity and Trading Activity? - CHORDIA, Tarun (Institutional Knowledge at Singapore Management University, 2014)
We examine whether the recent regime of increased liquidity and trading activity is associated with attenuation of prominent equity return anomalies due to increased arbitrage. We find that the majority of the anomalies have attenuated and the average returns from a portfolio strategy based on prominent anomalies have approximately halved after decimalization. We provide evidence that hedge fund assets under management, short interest and aggregate share turnover have led to the decline in anomaly-based trading strategy profits in recent years. Overall, our work indicates that policies to stimulate liquidity and ameliorate trading costs improve capital market efficiency.